Significance of Phosphate Nano-Fertilizers Foliar Application: A Brief Real-Field Study of Quantitative, Physiological Parameters, and Agro-Ecological Diversity in Sunflower - Dávid Ernst; Marek Kolenčík; Martin Šebesta; Ľuba Ďurišová; Samuel Kšiňan; Lenka Tomovičová; Nikola Kotlárová; Mária Kalúzová; Ivan Černý; Gabriela Kratošová; Veronika Žitniak Čurná; Jana Ivanič Porhajašová; et al. (Agronomy, 2023)
One of the challenges in agriculture practices is guaranteeing an adequate and bioavailable phosphorus supply for plants on phosphorus-deficient soils. A promising alternative lies in the utilization of phosphate nano-fertilizers (NFs) through spray applications. Therefore, this short-term study aimed to investigate the yet undetermined widespread impact of P-NFs on crops characterized by broad leaves, an intensive rate of photosynthesis, and belonging to the oilseed plant, sunflower (Helianthus annuus L.). To achieve this, NFs were applied at lower concentrations of various phosphate-based NFs, including (i) nano-hydroxylapatite (nano-Hap) and (ii) a mixture of nano-calcium zinc phosphate and macro-sized parascholzite (nano/macro-ZnPhos), in comparison to the NF-free control. The study was carried out under authentic field conditions during the 2022 vegetation season at the Dolná Malanta site within the Central European Region. The empirical evidence presented herein indicates that the utilization of biocompatible and bioactive nano-Hap, initially engineered for biomedical applications, and nano/macro-ZnPhos, now foliarly applied at reduced concentrations, elicited a statistically significant elevation in quantitative parameters and seasonal physiological responses. The parameters analyzed included head diameter, dry head weight, seed yield per hectare, nutritional seed oiliness, etc. as well as the physiological normalized difference vegetation index (NDVI), stomatal conductance index (Ig), and crop water stress index (CWSI). In terms of agro-ecological terrestrial bio/diversity, it was evident that the nano/macro-ZnPhos was the most hospitable variant for the terrestric insect community, but surprisingly, the agronomically more popular nano-Hap showed only statistically insignificant changes in the diversity of the detected communities. However, the relevance of outcomes highlighted using nano-fertilizers, supporting the concept of precision and sustainable agriculture under field conditions.